Cigarette smoke extract reduces FOXO3a promoting tumor progression and cell migration in lung cancer. (30th April 2021) - Di Vincenzo, Serena; Sangiorgi, Claudia; Ferraro, Maria; Buscetta, Marco; Cipollina, Chiara; Pace, Elisabetta
Abstract: Lung cancer is the leading cause of cancer death worldwide, and the carcinogens in tobacco smoke play a role in its progression and metastasis. The related molecular events are largely unknown. FOXO3a is a transcription factor considered a tumor suppressor. Its inhibition leads to cell transformation, tumor progression and metastasis. The aim of this study was to investigate, in different types of lung cancer cell lines (A549, COLO 699 N, SK-MES-1), the effects of cigarette smoke on mitochondrial status and cell metabolism and on key pathways involved in tumor progression and cell migration, looking at the role of FOXO3a in these mechanisms. The different lung cancer cells were exposed to cigarette smoke extract (CSE) and TGF-β1. Reactive oxygen species (ROS), mitochondrial superoxide, intracellular ATP, extracellular lactate, FOXO3a, p21, survivin, epithelial-to-mesenchymal transition (EMT) markers (E-cadherin, SNAIL1), MMP-9 and cellular migration were assessed by flow-cytometry, fluorimetry, western blot analysis, Real-Time PCR and scratch test. Our results showed that exposure to CSE: (i) increased ROS, mitochondrial superoxide, lactate release while reducing intracellular ATP; (ii) decreased FOXO3a and increased survivin and p21 in the cytoplasm; (iii) decreased E-cadherin, increased SNAIL1 and MMP-9 and promoted cell migration like TGF-β1 did. These effects could be partly explained by downregulation of FOXO3a, as demonstrated by silencing experiments. These data suggest that cigarette smoke induces oxidative stress and mitochondrial damage leading to metabolic reprogramming associated with increased glycolytic flux. This is accompanied with a downregulation of FOXO3a contributing to EMT processes and cell migration therefore promoting tumor progression.